Effective Synergistic Action of Benzimidazolium Nano Gemini Ionic Liquid and Conventional Surfactant for Chemical Enhanced Oil Recovery - Saien, Javad; Shokri, Behnaz; Kharazi, Mona (ACS omega, 2024)
Blends of newly developed Gemini surface-active ionic liquids (GSAILs) and conventional surfactants offer significant enhancements to the interfacial properties between crude oil and water, providing economic benefits in chemically enhanced oil recovery. In this study, the mixtures of a benzimidazolium cationic GSAIL, [C4benzim-C6-benzimC4][Br2], and sodium dodecyl benzenesulfonate (SDBS) were successfully utilized for improving crude oil–water interfacial properties. The research revealed synergistic effects of up to 99.6% in reducing interfacial tension (IFT), achieving a low IFT value of 0.04 mN m–1 corresponding to an optimal GSAIL mole fraction of 0.2 for the mixture of surfactants. Additionally, significant synergies of 53.4 and 74% were observed in oil–water emulsification and in surface wettability when using a GSAIL mole fraction of 0.2. These results showcase the importance of the dominant interaction between the opposite-charged surfactants. The Frumkin isotherm and the Rosen model were employed for the theoretical study of adsorption behavior of individual surfactants and their mixture at the interface, demonstrating reasonable parameter variations. The overall findings emphasize the potential of utilizing these unique blends to enhance oil recovery processes through tailored interfacial properties.